Harmonisasi Legislasi Pusat dan Daerah Melalui Penguatan Peran dan Fungsi Dewan PerwakilanRakyat Daerah (DPRD) di Bidang Legislatif: Indonesia - Novliza Eka Patrisia (Dialektika Publik, 2018)
This paper discusses the role and function of the DPRD, which bridges the local government with the people and seeks agreement and support for specific policies. This paper aims to find out how the legislation functions run by the DPRD, from the regional level to the central level. The problem encountered in this paper is how the legislative function of the DPRD itself, the obstacles encountered in the implementation of legislative functions, as well as efforts made to resolve the constraints. Furthermore, the results of this paper are analyzed by data analysis techniques in the form of descriptive with a clear sentence and can be understood in accordance with the purpose of writing. The results of the observation indicate that the legislative function of DPRD is running well and in accordance with the prevailing regulations, the community is involved in the deliberation process of the Raperda. The main obstacles encountered are still at least proposed of Raperda derived from the legislature. To overcome these obstacles, local governments and DPRD are making efforts to improve the human resources of the DPRD through education, training or comparative studies. Thus, it is expected that the DPRD can carry out the legislation function properly through the establishment of local policies or regulations